PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER DALAM OPERASI BENTUK AKAR - Mauliansyah, Anugrah; Halini, Halini; Monaldus, Monaldus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This research aimed to describe the improvement of understanding on scientific concepts and performance students of class X MA. Mathala'ul Anwar Pontianak school year 2016/2017 through the application of cooperative learning model of type Numbered Heads Together (NHT). This study is a qualitative descriptive Study conducted in MA. Mathala'ul Anwar Pontianak with 17 respondents. Data collection methods used are observation, interviews and tests. Study results: based on the percentage Score student performance at the first meeting it can be seen that the average student activity for each category that is visual of 86.27% (very active), oral of 58.82% (medium), heard of 88.23% ( Very active), and write of 100% (very active). At a meeting of the two can be seen that the average student activity for each category that is visual of 92.15% (very active), oral of 67.64% (active), heard of 100% (very active), and write of 100% (very active). Based on student test results, note that overall the students reach the learning k completeness Â of 17 students and 2 students who complete and 3 students are not to your satisfaction. General conclusions derived from this study was the use of cooperative learning model of type Numbered Heads Together (NHT) can improve the performance of students and scientific understanding scientific concepts in the material for students of class X MA. Mathala'ul Anwar Pontianak school year 2016/2017